Optimizing the Potential of Kebun Tinggi Tourism Village, Kampar Regency within the Framework of Village Autonomy - Mhd. Rafi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this article is to analyze how efforts to optimize the tourism potential of Kebun Tinggi Village in Kampar Regency are being implemented within the framework of village autonomy. The method used is a qualitative approach, with data collection techniques including interviews, documentation, and literature review. The results indicate that efforts to optimize the tourism potential of the village are being carried out by the village government through community participation and empowerment, particularly in the management and development of the Batu Tilam Waterfall tourist attraction. The inauguration of Kebun Tinggi Village as a tourism village has received considerable support from the supra-village government, which has supported and promoted it, resulting in economic and development impacts for the Kebun Tinggi community, although this is still not optimal. In other words, the optimization of Kebun Tinggi Village's tourism potential has met the characteristics of development implementation within the framework of village autonomy, and Kebun Tinggi Tourism Village is currently categorized as a developing tourism village.